2018
DOI: 10.1177/0022022117744892
|View full text |Cite
|
Sign up to set email alerts
|

Replication and Reproducibility in Cross-Cultural Psychology

Abstract: Replication is the scientific gold standard that enables the confirmation of research findings. Concerns related to publication bias, flexibility in data analysis, and high-profile cases of academic misconduct have led to recent calls for more replication and systematic accumulation of scientific knowledge in psychological science. This renewed emphasis on replication may pose specific challenges to cross-cultural research due to inherent practical difficulties in emulating an original study in other cultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 95 publications
2
42
1
1
Order By: Relevance
“…Research has shown that assets connecting work engagement and performance differs between contexts and populations (Halbesleben 2010;Shuck 2011). Specifically, the same asset which mediates or moderates a relationship in one context may not do so in another (Chan 1998;Fischer and Poortinga 2018;Milfont and Klein 2018). This phenomenon is clearly visible in contexts that are known to be highly volatile, extremely dynamic, exceedingly competitive, and subjected to continuous, rapid change (Milfont and Klein 2018;Smith and Haslam 2017), such as the ICT sector.…”
Section: Work Engagement and Task Performancementioning
confidence: 99%
See 3 more Smart Citations
“…Research has shown that assets connecting work engagement and performance differs between contexts and populations (Halbesleben 2010;Shuck 2011). Specifically, the same asset which mediates or moderates a relationship in one context may not do so in another (Chan 1998;Fischer and Poortinga 2018;Milfont and Klein 2018). This phenomenon is clearly visible in contexts that are known to be highly volatile, extremely dynamic, exceedingly competitive, and subjected to continuous, rapid change (Milfont and Klein 2018;Smith and Haslam 2017), such as the ICT sector.…”
Section: Work Engagement and Task Performancementioning
confidence: 99%
“…Various behavioral conditions and psychological assets connecting work engagement and performance is present in the literature (e.g. proactive behaviors, commitment, citizenship behaviors etc), however these are usually context specific (Milfont and Klein 2018). Where one asset might mediate or moderate the relationship within the ICT sector, the same might not be applicable within another context (Chan 1998;Fischer and Poortinga 2018;Milfont and Klein 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its adequate psychometric properties make it a good candidate for adaptation to other cultural contexts. Extension of its use would facilitate the replication, scienti c gold standard for the con rmation of results (Milfont & Klein, 2018). This framework pushes forward practical understandings of conservation con ict interventions by offering a novel, transdisciplinary, diagnostic tool for better understanding their complex, multifaceted variables (Harrison & Loring, 2020).…”
Section: Discussionmentioning
confidence: 99%